European Parliament elections in times of crisis - Francis Jacobs; Yves Bertoncini; Valentin Kreilinger; Stijn van Kessel; Andrea L. P. Pirro; Simon Otjes; Sonia Piedrafita; Vilde Renman (Intereconomics, 2014)
In May 2014, EU citizens will vote in the most important European Parliament elections to date. With the new powers allocated to it by the Lisbon Treaty, the new European Parliament will shape EU policies in many important areas and will elect the President of the Commission. However, public confidence in the EU has fallen to historically low levels - to a great extent due to the financial crisis and its aftermath - and the participation rate in European Parliament elections has dropped steadily since the first call for a direct vote in 1979. This raises fundamental questions about its political and democratic legitimacy. This Forum examines the economic agendas of the main political parties vying for power and the potential outcome of the May elections, including the role that radical and anti-euro parties are likely to play in the campaign and in the next Parliament.
Keywords: 330; Wahlkampf; Wahlverhalten; Wahlbeteiligung; Politische Partei; Partizipation; Macht; EU-Staaten